Seasonality of service provision in hip and knee surgery: A possible contributor to waiting times? A time series analysis - Upshur Ross EG; Moineddin Rahim; Crighton Eric J; Mamdani Muhammad (BMC, 2006)
Abstract Background The question of how best to reduce waiting times for health care, particularly surgical procedures such as hip and knee replacements is among the most pressing concern of the Canadian health care system. The objective of this study was to test the hypothesis that significant seasonal variation exists in the performance of hip and knee replacement surgery in the province of Ontario. Methods We performed a retrospective, cross-sectional time series analysis examining all hip and knee replacement surgeries in people over the age of 65 in the province of Ontario, Canada between 1992 and 2002. The main outcome measure was monthly hospitalization rates per 100 000 population for all hip and knee replacements. Results There was a marked increase in the rate of hip and knee replacement surgery over the 10-year period as well as an increasing seasonal variation in surgeries. Highly significant (Fisher Kappa = 16.05, p < 0.01; Bartlett-Kolmogorov-Smirnov Test = 0.31, p < 0.01) and strong (R2Autoreg = 0.85) seasonality was identified in the data. Conclusion Holidays and utilization caps appear to exert a significant influence on the rate of service provision. It is expected that waiting times for hip and knee replacement could be reduced by reducing seasonal fluctuations in service provision and benchmarking services to peak delivery. The results highlight the importance of system behaviour in seasonal fluctuation of service delivery.